Early Establishment of Native Vesicular-Arbuscular Mycorrhizas in Three Vegetable Crops of South India - A Comparative Study - Thomson T., Edathil; S., Maniam; K., Udaiyan (Universiti Putra Malaysia Press, 1994)
The vesicular-arbuscular mycorrhizal (VAM) status of three vegetable crops viz., tomato, brinjal and chilli was assessed during the initial establishment period in natural field conditions as well as in pot culture using nonsterile soil. The soil had low nutrient status and no manurial application was made during the 60 d course of the study. VAM fungal colonization in the roots was maximum at 45, 50, and 60 d after the respective germination of brinjals, tomato and chilli seeds under field conditions, and on the 60th d in the pot culture experiment. In no case was 100 per cent root colonization obtained. Ascending and descending trends in colonization were observed. In all cases, the original spore count of3.90 (±0.30) g dry soil increased markedly in the rhizosphere soil after plant growth. Spore number was more pronounced in pot than in field culture.